Pathology and behaviour in feline medicine: investigating the link between vomeronasalitis and aggression. Issue 12 (December 2016) - Asproni, Pietro; Cozzi, Alessandro; Verin, Ranieri; Lafont-Lecuelle, Céline; Bienboire-Frosini, Cécile; Poli, Alessandro; Pageat, Patrick
Objectives: The aim of the study was to investigate if the feline vomeronasal organ (VNO) can be affected by inflammatory lesions and if these changes are associated with behavioural alterations. Methods: VNOs from 20 cats were sampled during necropsy, submitted for routine tissue processing and stained with haematoxylin and eosin for histopathological evaluation. For the 20 cats, data on the presence of aggressive behaviours towards cats or humans were collected by questionnaire survey at the point of death. Inflammatory lesions were classified depending on the duration of the process as acute or chronic, both in vomeronasal sensory epithelium (VNSE) and in non-sensory epithelium (NSE). Fisher's exact test was used to compare VNO inflammation with behavioural data. Results: The VNSE was inflamed in 11/20 VNOs (55%) while the NSE was inflamed in 13/20 (65%). Overall, the VNO was affected by inflammation in 14/20 (70%) cats, and all the lesions were classified as chronic. Five out of 20 cats (25%) had documented intraspecific aggressive behaviours and 8/20 (40%) had shown aggression towards humans. Fisher's exact test showed a statistically significant correlation between inflammation of the VNSE and intraspecific aggression ( P = 0.038). No statistically correlations were observed between VNSE inflammation and aggression towards humans and between NSE inflammation and aggression towards cats or humans. Conclusions and relevance: Our results show, for the first time, the existence of vomeronasalitis in animals and its possible association with intraspecific aggressive behaviours. The inflammatory microenvironment could impair VNSE functionality, causing intraspecific communication alterations, probably through a reduction in chemical communication action and perception. Owing to the pivotal role of the VNO in the social life of cats and other species, this report provides a rationale to further investigate this disease in relation to a variety of behavioural disorders.